N, P‐Heterocyclic Germylene/B(C6F5)3 Adducts: A Lewis Pair with Multi‐reactive Sites. Issue 5 (22nd December 2016) - Del Rio, Natalia; Lopez‐Reyes, Morelia; Baceiredo, Antoine; Saffon‐Merceron, Nathalie; Lutters, Dennis; Müller, Thomas; Kato, Tsuyoshi
Abstract: An N, P‐heterocyclic germylene/B(C6 F5 )3 Lewis adduct 2 presenting multi‐reactive sites (P/B Lewis pair, germylene, Ge=P π‐bond) is reported. In contrast to classical frustrated Lewis pairs or divalent Group 14 element species, 2 is able to activate two small molecules simultaneously. Of particular interest, 2 reacts with silanes leading to the formation of original cationic germylenes 3, and can be used as a metal‐free catalyst for selective CO2 ‐hydrosilylation to H2 C(OSiEt3 )2 . Abstract : Multitasking : An N, P‐heterocyclic germylene/B(C6 F5 )3 Lewis adduct presents multi‐reactive sites (Lewis pair, germylene, Ge=P π‐bond). In contrast to simple frustrated Lewis pairs or divalent Group 14 element species, the germylene adduct is able to activate two small molecules simultaneously. This unique property was successfully applied to selective and metal‐free catalytic CO2 hydrosilylation to H2 C(OSiEt3 )2 .